MANHAJ HAJI ABDUL RAHMAN LUBUK TAPAH DALAM PENULISAN ILMU FIQH: TUMPUAN TERHADAP KARYA PEDOMAN SOLAT BERJEMAAH: Haji Abdul Rahman Lubuk Tapah’s Method in Writing Fiqh: Focus on Pedoman Solat Berjemaah - Mustapha, Ahmad Murshidi; Daud, Mahyudin (Jurnal Syariah, 2018)
The development of madrasa (Islamic traditional institution) in Kelantan has produced many pious figures particularly in Islamic studies in classic scripture concept. Local Muslim scholars specialized in Islamic studies had contributed to these institutions whether by establishing their own madrasah or teaching at present madrasah. This research is conducted to present the personal biography of Haji Abdul Rahman Lubuk Tapah, Pasir Mas, Kelantan and his writing entitled â€œPedoman Solat Berjemaahâ€œ. He is seen as a major contributor to traditional religious study in Kelantan and his influence is still lively due to legacy of his great writings. Generally, this is a library-based research which using main sample based from the book of â€œPedoman Solat Berjemaahâ€. His writing structure ease readers to understand the content and to answer any questions related to rules and regulation of congregational in á¹£alÄh. The varieties of concept shown by Haji Abdul Rahman has made his book as the most favoured book especially in abode study until present time.